CXCR4 Overexpression in Human Adipose Tissue-Derived Stem Cells Improves Homing and Engraftment in an Animal Limb Ischemia Model - Kim, Mijung (Cell Transplant, 2017)
We investigated the effects of transplantation of CXCR4-overexpressing adipose tissue-derived stem cells (ADSCs) into a mouse diabetic hindlimb ischemia model on homing and engraftment as early as 48 h after transplant. CXCR4-overexpressing ADSCs were intramuscularly or intravenously injected into diabetic mice with hindlimb ischemia. After 48 h, muscle tissues in the femur and tibia were collected, and the CXCR4 expression pattern was analyzed by immunofluorescence staining. The homing and engraftment of transplanted CXCR4-overexpressing ADSCs into the ischemic area were significantly increased, and intravenous (systemic) injection resulted in the more effective delivery of stem cells to the target site 48 h posttransplantation. Furthermore, CXCR4-overexpressing ADSCs more efficiently contributed to long-term engraftment and muscle tissue regeneration than normal ADSCs in a limb ischemia model. In addition, the homing and engraftment of ADSCs were correlated with the CXCR4 transfection efficiency. These results demonstrated that enhanced CXCR4 signaling could significantly improve the early homing and engraftment of ADSCs into ischemic areas as well as the long-term engraftment and ultimate muscle tissue regeneration.